SAVE-CLC: An Intervention to Reduce Suicide Risk in Older Veterans following Discharge from VA Nursing Facilities. Issue 1 (2nd January 2020) - Luci, Katherine; Simons, Kelsey; Hagemann, Lauren; Jacobs, M. Lindsey; Bower, Emily S.; Eichorst, Morgan K.; Hilgeman, Michelle M.
ABSTRACT: Objective : We describe the development and implementation of a telephonic intervention (SAVE-CLC) piloted at three VA sites for Veterans returning to the community from VA nursing facilities (Community Living Centers or "CLCs"). Care transitions present a known period of medical risk for older adults and may pose increased risk for suicide. Veterans discharging from CLCs are at elevated risk compared to age and gender matched controls. Methods : Using a quality improvement approach, input was gathered from key stakeholders to aid in the development of the intervention. Veterans were screened for depressive symptoms and need for additional support by phone. Results : Of the Veterans who received the SAVE-CLC intervention, 87.9% had at least one prior mental health diagnosis, though only 19.7% had an outpatient mental health appointment arranged at CLC discharge. Results suggest that the intervention is feasible across multiple outpatient settings and is generally well-received by Veterans and caregivers, with 97% of those contacted reporting that the telephone calls were helpful. Conclusion : This flexible, telephone-based intervention addresses the unmet need of integrating mental health care into discharge planning during care transitions. Clinical Implications : SAVE-CLC offers a feasible and acceptable solution to suicide risk in older Veterans exiting a CLC.